The urban renewal of Marrakech: two religious complexes of the Saadian period - Almela Legorburu, Iñigo (Anaquel de Estudios Árabes, 2020)
Once the Saadian power was consolidated in al-Maghrib al-Aqsà and the capital was established in Marrakech, Sultan ʿAbdallāh al-Gālib (1557-1574) led one of the most splendid moments of the dynasty. So much so, that he undertook a set of works to reform and equip the city, which had been relegated to a secondary role and had suffered a regression throughout the fifteenth century. Among the works of this Sultan are the reorganization of the city as well as the construction of infrastructures and monumental buildings that became important referents within the urban landscape. In the present paper, all the known works that formed part of the ʿAbdallāh project are outlined, in order to recognize the historical relevance of his government. However, our main aim is to present two religious complexes located in the medina, which reproduce the same architectural model and implementation pattern. In both cases, the design of the complex and its relation with the environment has been analysed, in order to evaluate the impact that its construction entailed in the urban landscape and in the development of the city.